Antimicrobial Activity of Chemically Modified Anionic Azo Dyes and Their Potential for Treating Infectious Diseases - Mohammed, Aliyu Danmusa; Basiru, Aliyu (Pharmaceutical Reports, 2025)
This study explores the synthesis, characterization, and antimicrobial evaluation of quaternary ammonium salts (QAS) and silver nanoparticles (AgNPs) incorporated with azo dyes—Sunset Yellow, Tartrazine, and Allura Red. FTIR spectroscopic studies confirmed key functional groups and interactions, including azo (–N=N), C=C, and hydroxyl stretches, indicating successful conjugation between dyes and carrier materials. The antimicrobial activities of these compounds were assessed against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, and Salmonella spp. Results revealed enhanced inhibition zones, particularly for the dye incorporated with siver nanoparticles (dye-AgNPs) combinations, with Tartrazine + AgNPs (B2) showing the highest efficacy against S. aureus. Quaternary ammonium salts alone displayed moderate activity, while their combinations with azo dyes yielded improved bacterial inhibition, especially against Gram-positive strains. The enhanced antimicrobial performance is attributed to increased lipophilicity and better penetration of bacterial membranes due to dye incorporation. Furthermore, the research highlights the potential use of azo dye-functionalized QAS and AgNPs as effective antimicrobial agents, especially in targeting resistant Gram-positive pathogens.